Driving status of patients with generalized spike-wave on EEG but no clinical seizures - Antwi, Prince (Epilepsy Behav, 2018)
Generalized spike-wave discharges (SWD) are the hallmark of generalized epilepsy on the electroencephalogram (EEG). In clinically obvious cases, generalized SWD produce myoclonic, atonic/tonic or absence seizures with brief episodes of staring and behavioral unresponsiveness. However, some generalized SWD have no obvious behavioral effects. A serious challenge arises when patients with no clinical seizures request driving privileges and licensure, yet their EEG shows generalized SWD. Specialized behavioral testing has demonstrated prolonged reaction times or missed responses during SWD, which may present a driving hazard even when patients or family members do not notice any deficits. On the other hand, some SWD are truly asymptomatic in which case driving privileges should not be restricted. Clinicians often decide on driving privileges based on SWD duration or other EEG features. However, there are currently no empirically-validated guidelines for distinguishing generalized SWD that are “safe” versus “unsafe” for driving. Here we review the clinical presentation of generalized SWD and recent work investigating mechanisms of behavioral impairment during SWD with implications for driving safety. As a future approach, computational analysis of large sets of EEG data during simulated driving utilizing machine learning could lead to powerful methods to classify generalized SWD as safe vs. unsafe. This may ultimately provide more objective EEG criteria to guide decisions on driving safety in people with epilepsy.